Dampak Kelas Sosial pada Kelanjutan Pendidikan Anak di Desa Nunmafo - Yohana Hati Bimeku (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2025)
The study aims to determine (1) the impact of social class structure on sustained children's education of Nunmafo Village, and (2) the supporting factors of social class structure on sustained children's education of Nunmafo Village. This is qualitative research where parents and children in Nunmafo Village became subject of the study. The data were collected through observations, interviews, and documentations. The data were validated using triangulation of source, technical, and time. The results showed that social class structure has an impact on children's sustainability education in Nunmafo Village. Children in the upper class receive quality education and teachers, but they are more concerned with business than education. Middle-class families can satisfy their children's educational demands, but they do not receive high-quality education and teachers. Children in society have high expectations but are limited by financial constraints. While supportive variables include: (1) restricted access to educational resources, (2) economic demands, (3) a lack of family support, and (4) a lack of motivation among children. So it can be concluded that differences in social class structure have an important message in determining children`s educational success.